2016
DOI: 10.1016/j.jmii.2014.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of clinical outcomes in pediatric bacterial meningitis focusing on patients without cerebrospinal fluid pleocytosis

Abstract: In children with bacterial meningitis, nontypical CSF findings and, in particular, normal CSF leukocyte count and increased protein level may indicate a worse prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 26 publications
4
23
1
Order By: Relevance
“…In this study, 135(68.9%) patients were investigated for their CSF, and among them, 84 (62.2%) of meningitis patients had an elevated level of WBC. Similar studies were done Felege Hiwot Referral Hospital [13], and in Taiwan [18] indicated that most admitted patients tested their CSF, which was about 69.8% and 88%, respectively. Among them, 98.3% and 83.8% had elevated WBC, respectively.…”
Section: Discussionsupporting
confidence: 72%
“…In this study, 135(68.9%) patients were investigated for their CSF, and among them, 84 (62.2%) of meningitis patients had an elevated level of WBC. Similar studies were done Felege Hiwot Referral Hospital [13], and in Taiwan [18] indicated that most admitted patients tested their CSF, which was about 69.8% and 88%, respectively. Among them, 98.3% and 83.8% had elevated WBC, respectively.…”
Section: Discussionsupporting
confidence: 72%
“…This appears to be the largest study evaluating the frequency, clinical characteristics, and outcomes of patients without CSF pleocytosis in five types of CNS infection. Previous studies have described case series of patients without CSF pleocytosis in relation to bacterial meningitis, herpes simplex encephalitis, and enteroviral meningitis (Saraya et al, 2016;Hui Tan et al, 2016;Lin et al, 2016). The lack of CSF pleocytosis in bacterial meningitis is rare, but this can be seen more commonly in viral infections.…”
Section: Discussionmentioning
confidence: 99%
“…Patients without CSF pleocytosis appeared to have a high rate of unfavorable outcomes, including sequelae and death. A recent study of 175 children with bacterial meningitis (Lin et al, 2016) identified the lack of CSF pleocytosis as a prognostic factor in the multivariable analysis. The examining clinician should not underestimate the presence of a CNS infection despite the lack of CSF pleocytosis for a patient with a suspicion of meningitis or encephalitis.…”
Section: Discussionmentioning
confidence: 99%
“…However, these parameters are often misleading, with an absence of pleocytosis (1-12% of cases) or predominant mononuclear cells (Bratlid and Bovre, 1977;Koutroumanidis et al, 2000;Hase et al, 2014). In one study, out of 645 patients with bacterial meningitis 7% of patients did not have pleocytosis (van de Beek et al, 2004;Lin et al, 2014;Mentis et al, 2016). Furthermore, these two parameters have low discriminatory power between bacterial versus viral meningitis.…”
Section: Quantitative Csf Analysis: Cells and Chemistrymentioning
confidence: 99%